THE PHONEMES OF PORTUGUESE - Massini-Cagliari, Gladis [UNESP] (Taylor & Francis, 2024)
This chapter aims to provide a description of vocalic and consonantal phonemes in Portuguese, correlating them with their phonetic realization in different varieties of the language. As will be shown, Brazilian Portuguese (BP), European Portuguese (EP), and the varieties spoken in Africa (AfrP) and Asia (AsP) do not differ with regard to their phonemic inventory, despite differences at the phonetic level. Because of the great variability in Portuguese pronunciation in the four continents where the language is spoken, this chapter focuses on phonetic phenomena from different varieties, particularly Southeastern BP and Lisbon EP. With respect to vowels, Portuguese has seven contrastive segments in stressed position, with phonetic variability in pretonic and unstressed positions. The phonological status of nasal vowels is also discussed. With regard to the consonantal system, a group of 19 phonemes are presented, with focused discussion on rhotics, palatals,/t, d/-palatalization, and coda-sibilant palatalization and voice neutralization.